The Unity of Reality: God, God-Experience and Meditation in the Hindu-Christian Dialogue (transl. from the German Original by J.V. Zeitz) - Athappilly, Sebastian (Journal of Dharma, 1993)
Michael von Bruck, The Unity of Reality: God, God-Experience. and Meditation in the Hindu-Christian Dialogue (transl. from the German Original by J.V. Zeitz), New York: Paulist Press, Mahwah, 1991, pp. vi + 340.